State Interests, Migration and the European Court of Human Rights - Almqvist, Jessica; Thorburn Stern, Rebecca (European Policy Analysis, 2026)
This European Policy Analysis examines recent developments within the Council of Europe concerning a proposed political declaration by its Committee of Ministers on the European Court of Human Rights’ approach to migration-related issues. These developments follow an Open Letter in May 2025 and a subsequent Joint Statement by a group of member states expressing concerns about the Court’s case-law and the balance between migrant rights and state interests. The analysis focuses on the intergovernmental process leading to the draft declaration, including the discussions within the Steering Committee for Human Rights and the role of the Committee of Ministers, and situates the current initiative in the context of earlier high-level declarations concerning the Court. The paper identifies key areas of disagreement, particularly regarding references to migration, state responsibilities, and the Court’s interpretative role. It shows that the drafting process has been characterised by extensive negotiations and a persistent lack of consensus. The authors argue that the significance of the initiative lies less in its potential legal effects than in its symbolic and institutional consequences. A declaration aligned with the more critical positions risks undermining the perceived independence and authority of the Court, thereby affecting the broader legitimacy of the Convention system.
Keywords: Human rights; Mänskliga rättigheter